Using T –Chart Technique To Improve Students’ Reading Comprehension - Muhammad Suhaili; K. Dedy Sandiarsa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
This research aimed to describe the use of T –chart Technique to improve students’ reading comprehension. This Classroom Action Research was conducted at the first grade students of MA NW PUTRI NARMADA with 27 students where the all of students are female.  This research focus on the students reading comprehension. It consists of two cycles which is in the cycle consisting of planning, action, observation, reflecting. The data gathering used multiple choice and analyzed the data are using qualitative and quantitative approach, in the first cycle wasn’t improve students reading comprehension where the mean score of pre-test was 61 with the percentage 14% and the post-test was 69 with the percentage 33%, the result of the second cycles where the mean score of pre-test was 70 with the percentage 44% and the mean score of post-test was 86 with percentage 85%. The result of students’ achievement in cycles II with passing scores in the first were 33% (not good) and the second test were 85% (very good) indicated the target of 75 of the minimum criteria has been achieved. Based on the result of the study, it can be concluded that the use of T –chart technique to improve students’ reading comprehension at MA NW PUTRI NARMADA in academic year 2018/2019 are success